Kepastian Hukum Terhadap Sertifikat Elektronik Hak Milik Atas Tanah - Afif, Yuzi; Afif Mahfud, Muhammad (UNES Law Review, 2023)
This study examines the juridical analysis of the legal force of property rights certificates based on the Minister of Agrarian Affairs/Head of BPN no. 1 of 2021. The research method used is normative juridical study, namely research studies based on legal sources such as laws and regulations, and expert opinion to research studies related to the title chosen by the researcher. The result of this research is that the transformation of technological advances has shifted the land registration system from paper-based to electronic. One of them is the issuance of electronic certificates contained in the ATR/Head of BPN Ministerial Regulation Number 1 of 2021. This electronic certificate refers to the legal source, namely the Electronic Information and Transaction Law and the Job Creation Law, which is not a problem because it only regulates electronic certificates.